The Effect of Argumentation-Based Inquiry Approach Supported by Metacognitive Activities on Science Achievement of Preservice Teachers - KABATAŞ MEMİŞ, Esra; BOZKURT AYDIN, Rahşan (Kastamonu Egitim Dergisi, 2022)
Purpose: This study was conducted with students in their third year at the Department of Science Teaching at Kastamonu University in the 2015-2016 academic year. The study's objective is to investigate the effect of the argumentation-based and argumentation-based inquiry approaches supported by metacognition activities on students' science achievement.Design/Methodology/Approach: The study was carried out in 10 weeks with the participation of 69 students divided into three groups, namely, the ABI group, the ABI + metacognitive activity group and the group in which the traditional method was applied. An achievement test consisting of 25 questions and semi-structured interviews were used as data collection tools. In the data analysis, pre-post test evaluations and descriptive statistics were used.Findings: The data obtained showed that there was a significant difference between the groups, which was in favour of groups where the ABI approach was applied, and that there was a slightly significant difference between groups of ABI and the ABI supported by metacognition activities, which was in favour of the ABI group supported by metacognition activities. The interviews with students revealed many significant and positive outcomes; they stated that they were satisfied with the ABI applications, that they would prefer ABI in their professional lives, and that the applications facilitated scientific thinking.Highlights: Metacognition has an important place in scientific literacy and knowledge structuring. Because it provides metacognition to be aware of the individual's learning and learning process, it can be said that language practices such as discussion and writing, especially in the ABI process, activate cognitive and metacognitive mechanisms.
Keywords: Argument Based Inquiry (ABI); Metacognition; Eğitim Üzerine Çalışmalar; Studies on Education; Argument Based Inquiry (ABI); Metacognition; Science achievement; 4. Education